2021
DOI: 10.3390/foods10050986
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne TiO2 Nanoparticles Induced More Severe Hepatotoxicity in Fructose-Induced Metabolic Syndrome Mice via Exacerbating Oxidative Stress-Mediated Intestinal Barrier Damage

Abstract: The hazard of titanium dioxide nanoparticles (TiO2 NPs) in diseased population should be given focus due to the huge number of these NPs in foods and medicine. This study aimed to evaluate the stronger biological adverse effect of oral exposure to TiO2 NPs in a fructose-induced metabolic syndrome mouse model. Compared to the normal mice, low-dose (2 mg/kg) TiO2 NPs did not cause severe hepatotoxicity. However, high-dose (20 mg/kg) TiO2 NPs induced aggravated hepatic inflammation, fibrosis, and apoptosis, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
5
13
0
Order By: Relevance
“…33 Thus, fructose can not only increase the accumulation of lipid produced de novo but also activate the body's oxidative stress response directly. 34,35 Cho et al 36 demonstrated that high fructose drinking can induce ROS overproduction and result in low-grade inflammation in the liver and intestine, consistent with our findings.…”
Section: ■ Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…33 Thus, fructose can not only increase the accumulation of lipid produced de novo but also activate the body's oxidative stress response directly. 34,35 Cho et al 36 demonstrated that high fructose drinking can induce ROS overproduction and result in low-grade inflammation in the liver and intestine, consistent with our findings.…”
Section: ■ Discussionsupporting
confidence: 92%
“…The “burden” conditions of liver in MetS mice regularly result from the translation of 22% percent of fructose to an unstable five-membered ring structure in solution . Thus, fructose can not only increase the accumulation of lipid produced de novo but also activate the body’s oxidative stress response directly. , Cho et al demonstrated that high fructose drinking can induce ROS overproduction and result in low-grade inflammation in the liver and intestine, consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have reported that nanomaterial injection is linked to the development and exacerbation of NAFLD in mice ( Jia et al, 2017a ; Jia et al, 2017b ; Zhao et al, 2021 ; Zhu et al, 2021 ). Oral exposure to AgNPs caused no general toxicity in normal mice and aggravated the progression of fatty liver disease to steatohepatitis only in overweight mice through enhancement of liver inflammation and suppression of hepatic fatty acid oxidation ( Jia et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the liver is the most prominent organ for the sequestration and accumulation of nanomaterials, indicating a substantial hurdle for the delivery of nanodrugs and raising hepatotoxicity ( Zhou et al, 2020 ; Chen et al, 2021 ; Zhu et al, 2021 ). In light of the current literature, nanomaterials deposited in the liver decrease hepatocyte survival rate, induce oxidative stress, mitochondrial damage, inflammatory cell infiltration, and even autophagy, apoptosis, pyroptosis, or other forms of cell death ( Cornu et al, 2020 ; Zhao et al, 2021 ). Our previous study showed that the deposited nanoparticles in the liver disturb the activity of hepatic drug-metabolic enzymes and transporters, which increases the risk of inflammation-mediated liver injury in mice ( Zhou et al, 2020 ; Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mouse experiments, after intragastric administration, TiO 2 -NPs were absorbed by the gastrointestinal tract [131] and accumulated in the spleen and liver [132,133]. TiO 2 -NPs have been shown to damage multiple organs of mice (intestine [134], liver [135], spleen [136], kidney [137], etc.) by inducing cell injury and changing the expression of inflammatory cytokines [138][139][140][141].…”
Section: Prospective Applications and Challenges Of Nano-tio 2 In Den...mentioning
confidence: 99%